Characterization of Zinc Oxide Nanoparticle from Waste Cooking Oil for Surface Coating (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
The use of nanoparticles (nps) for surface coating has increased the researcher's interest in it due to its inherent properties, especially from metal oxide such as zinc oxide (ZnO). It is ideal for combining the coating solution because of its low cost and smaller pigments. Bio-organic materials are used for synthesis of ZnO to produce green or eco-friendly products as well as to replace polymers derived from traditional petroleum. This study aimed to incorporate ZnO into the surface coating with its potential properties to be used as an effective surface coating material. This study was focused on the synthesis of ZnO from waste cooking oil (WCO) via encapsulation of ZnO with APO obtained from WCO, followed by characterization and testing for its suitability in surface coating application. The characteristics of ZnO nps were studied by using the infrared spectroscopy of Fourier transformation (FTIR), x-ray diffraction (XRD), UV spectrum (UV-Vis) and scanning electron microscope (SEM). FTIR analysis is unable to confirm the existence of ZnO nps because it does not show maximum absorption at wavelength of 421 cm-1. X-ray (XRD) shows the particles are in high amorphous conditions. ZnO nps exhibits UV-VIS absorption at a wavelength 330 nm that provides anti-UV property. Analysis from SEM showed Zn element is absent in the dispersion of ZnO-APO paint morphology. In addition, the effectiveness of the antibacterial properties of the ZnO nps for surface coating does not show any inhibition of the bacteria, methicillin-resistant Staphylococcus aureus (MRSA) and Klebsiella pneumoniae (K. pneumoniae). Therefore, better methods of production need to be examined to help in the encapsulation of ZnO nps. The suitability of the organic or inorganic surface coating material is also needed to be explored in by further characterizing the materials based on its composition, strength and effectiveness.
Keywords: ZnO nanoparticles; low cost; surface layer; green process; antibacterial